Освітня діяльність купецьких товариств Львова у 20-х – 30-х рр. ХХ ст. - Безсмертний, А. С. (НТУ "ХПІ", 2014)
Cтаття присвячена дослідженню освітньої діяльності купецьких товариств міста Львова у сфері професійної підготовки своїх членів та підвищення їх кваліфікаційного рівня. Така діяльність здійснювалася шляхом організації навчальних курсів та налагодження співпраці із львівськими освітніми закладами. Проводячи її, керівники купецьких організації намагалися підняти в суспільстві престиж професії купця, ставлення до якої в суспільстві було вкрай негативне.

Article is sanctified to research of educational activity of merchant societies of Lviv in the field of professional preparation of the members and increase of them qualifying level. Such activity was conducted by organization of educational courses and adjusting of collaboration with Lviv educational establishments. Conducting such activity, the leaders of merchant to organization tried to heave up in society prestige of profession of merchant, attitude toward that was extremely negative. Quite a bit merchants were considered swindlers and easy riders that cheat customers. Despite this merchant organizations managed to change attitudes in society itself and to improve the professional, and educational level of merchants.
Educational activities Lviv merchant associations in 20-th – 30-th yeraes of XX century
Keywords: Cоюз Українських Купців; Україна історія; міжвоєнний період; 20–30 рр. ХХ ст.; Купецька Конгрегація; торгово-галузеві курси; Львів; Lviv; interwar period; trade and industry courses; Merchants Congregation; Union of Ukrainian Merchants